Intervensi MBCT (Mindfulness-Based Cognitive Therapy) pada Pasien Ansietas: a Scoping Review - Indra Maulana; Hendrawati Hendrawati; Iceu Amira; Sukma Senjaya (Malahayati Nursing Journal, 2022)
ABSTRACT Anxiety is a feeling of uneasiness, worry, fear that is uncertain and can be triggered by unknown things or new experiences. Intervention in anxiety can be done with MBCT (Mindfulness-Based Cognitive Therapy). This therapy combines cognitive behavioral techniques with mindfulness strategies to help individuals better understand and manage their thoughts and emotions to achieve relief from feelings of anxiety The aims of this study is to analyze the MBCT (Mindfulness-Based Cognitive Therapy) intervention that is able to reduce anxiety. The research used is a literature review study with literature searches carried out on the Pubmed, ScienceDirect, CINAHL, Proquest databases. Using keywords that have been determined and selected based on inclusion and exclusion criteria, 8 articles were found that were appropriate and suitable for use in the literature study. From the search results, 8 articles were found that discussed being able to reduce anxiety in various populations and types of MBCT. This intervention can not only reduce anxiety, it can also reduce levels of depression, distress, functional impairment, and fatigue as well as improve adaptive emotion regulation and psychological well-being. The results of this literature study are expected to develop or become a renewal of research on MBCT (Mindfulness-Based Cognitive Therapy) interventions to treat patients who experience psychosocial anxiety problems. Keyword: MBCT, Anxiety, Anxiety Reduction  ABSTRAK Ansietas merupakan perasaan was-was, khawatir, takut yang tidak menentu dan dapat dipicu oleh hal yang tidak diketahui atau terhadap pengalaman baru. Intervensi pada ansietas dapat dilakukan dengan MBCT (Mindfulness-Based Cognitive Therapy). Terapi ini gabungan dari teknik perilaku kognitif dengan strategi perhatian untuk membantu individu lebih memahami dan mengelola pikiran dan emosi mereka untuk mencapai bantuan dari perasaan cemas, tujuan dari penelitian ini adalah untuk menganalisis intervensi MBCT (Mindfulness-Based Cognitive Therapy) yang mampu menurunkan ansietas. Penelitian yang digunakan adalah studi literatur review dengan pencarian literatur  dilakukan pada database Pubmed, ScienceDirect, CINAHL, Proquest. Menggunakan kata kunci yang telah ditentukan dan dipilih berdasarkan kriteria inklusi dan eksklusi, didapatkan 8 artikel yang sesuai dan layak digunakan dalam studi literatur. Dari hasil pencarian di dapatkan 8 artikel yang membahas mampu menurunkan ansietas dari berbagai populasi dan jenis MBCT. Intervensi ini tidak hanya dapat menurunkan kecemasan, juga dapat menurunkan tingkat depresi, distress, gangguan fungsional, dan kelelahan serta meningkatkan regulasi emosi adaptif dan kesejahteraan psikologis. Hasil studi literatur ini diharapkan dapat mengembangkan atau menjadi pembaharuan penelitian mengenai intervensi MBCT (Mindfulness-Based Cognitive Therapy) untuk menangani pasien yang mengalami permasalahan psikososial ansietas. Kata kunci: MBCT, Ansietas, Penurunan Ansietas